PENGARUH PRODUK DOMESTIK REGIONAL BRUTO (PRDB), INDEKS PEMBANGUNAN MANUSIA (IPM), DANA PIHAK KETIGA PERBANKAN SYARIAH (DPK), INDEKS KUALITAS LINGKUNGAN HIDUP (IKLH), DAN DANA ALOKASI KHUSUS (DAK) TERHADAP PERKEMBANGAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Salma Fauziyah; Rina Trisnawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to examine the effect of Gross Regional Domestic Product, Human Development Index, Islamic Banking Third Party Fund, Environmental Quality Index, and Special Allocation Fund on Sustainable Development Goals in Indonesia. The sampling technique used was purposive sampling with a sample of 476 district and city in Indonesia in 2018-2021. This research data uses secondary data obtained through the website of the Central Statistics Agency, the Directorate General of Fiscal Balance, and the Financial Services Authority. The analytical method used is multiple linear regression. The results showed that the Human Development Index and Special Allocation Fund had a positive effect on Sustainable Development Goals. Gross Regional Domestic Product and Environmental Quality Index had a negative effect on Sustainable Development Goals. Meanwhile, Islamic Banking Third Party Funds had no effect on Sustainable Development Goals.